The Contribution of Cash Waqf in Improving Programs in the Field of Education (Study at the International Islamic University (IIUM Endowment Fund) Malaysia) - Arifani, Devina; Rozihan, Rozihan (JURNAL AKTA, 2024)
Waqf is one of the financial instruments in Islam that has great potential to support various sectors, especially in the field of education. Education is one of the main pillars in community development. With the increasing need for quality education, adequate resources are very important. However, many educational institutions, including IIUM, face challenges in terms of funding. This is where cash Waqf can make a significant contribution. This study aims to analyze the Contribution of Cash Waqf in Improving Programs in the Field of Education (Study at the International Islamic University (IIUM Endowment Fund) Malaysia). The research method used is a qualitative descriptive analytical method. The results of this study are that Waqf has great potential in improving the welfare of Muslims and even reaching non-Muslims, not only infrastructure development but also improving education because the principles of Waqf and knowledge must be continuous and must not run out.